Transitional Space as Solution for Occupants Safety: Learning from the Past - Ami Arfianti; Murni Rachmawati; Purwanita Setijanti (Future Science, 2020)
This paper aims to show that for the safety of the occupants in today's architecture, we could learn from the spatial arrangement of the past architecture. In this paper, the adoption of the historiography method from historians was used to trace the genealogy of past architecture. Historiography is a method that is used to trace history back to the past to understand the past. By using historiography, the genealogy (line of a descendant) of vernacular Javanese building will be traced to find the transitional space in the spatial arrangement of the complex of housing. And then, the genealogy of vernacular Japanese buildings will be traced too, to find the transitional space in their spatial arrangement housing. To represent the European building, the genealogy of the Greek building will be used. Again, transitional space will be traced in their building. After that, the finding from these tracing will be compared to find the similarity and differences of the transition spaces. The result of this study showed that people from countries of samples did not design their building with open access to the spatial arrangement. There is always a transitional space from outside of the building to inside of the building. Because open access will make the occupants of the building prone to safety. Not only from tangible (physical) threats but also the intangible threats.